Pengaruh Pemberian Kombinasi Pupuk NPK Majemuk Dan Pupuk Daun Terhadap Pertumbuhan dan Hasil Tanaman Sawi Hijau (Brassica juncea Var. Shinta) - Ardhayani, Iswi; Syafi,i, Muhammad; Rahayu, Yayu Sri (UNIVERSITAS LABUHANBATU, 2023)
The prediction of the development trend of mustard greens consumption in Indonesia in the next 10 years (2020 to 2029) has a tendency to increase. The use of compound NPK fertilizers and foliar fertilizers can be a good solution and alternative in increasing the production of mustard greens. This research was conducted at Baraya Garden Putra, Cisarua District, Sumedang Regency from June to July 2023. The method used was an experiment with a single factor randomized block design (RBD) with 11 treatments and 3 replications. The treatment consisted of compound NPK fertilizer (100 kg/ha, 200 kg/ha, and 300 kg/ha) combined with foliar fertilizer (1 g/l, 2 g/l, 3 g/l). The results of the study were analyzed using the F test at the 5% level to find out the best treatment, followed by the Duncan Multiple Range Test (DMRT) at the 5% level. The results showed that the application of compound NPK fertilizer combined with foliar fertilizer made a significant difference to the growth and yield of mustard greens. The K treatment with a combination of 300 kg/ha compound NPK fertilizer and 3 g/L foliar fertilizer obtained the highest results on the parameters of plant height, number of leaves, leaf area per plant, leaf greenness level, fresh weight per plant, and crown wet weight. Â Keywords : compound NPK fertilizer, foliar fertilizer, mustard greens